Metacognition and Self-determination, Impulsivity and Emotional intelligence, and its relation with wellbeing and health indicators in young adults - Castro Muñoz, John Alexander (2021)
Background: From the evidence, it is inferred the influence of cognitive or motivational variables over the emotional ones and from these on the perception and self-reported wellbeing and health, with direct implications for health promotion and prevention. Method: a quantitative approach, descriptive, correlational cross-sectional with statistical explanatory analysis investigation was conducted, analyzing the data through path modeling of the partial least squares approach of the structural equations model, by using the Smart PLS software 3.3.2 version, analyzing consequently the convergent and discriminant validity of the model. A total 223 undergraduate university young adult students was evaluated, 41 men (18,4%) and 182 women (81,6%) with ages between 18 and 30 years old (µ= 24,26 y σ=±3,30), from Bogotá Colombia participated. Results: The results allowed to significant relations between the self – determination with the impulsivity and emotional intelligence, and from these with the psychological well-being and healthy habits. There were not identified significant relations between the metacognition and the impulsivity, although there are between metacognition and emotional intelligence. Conclusions: The proposed model about the significant relations between metacognition and self-determination with impulsivity and emotional intelligence and between these and the psychological well-being and healthy habits was confirmed. The specific result related to the absence of significant relations between metacognition and the impulsivity suggest for futures research, to emphasize on the metacognitive process implicated on the emotional components. The results are discussed, its implications and the necessity to be considered more determinants for the promotion of health.